Sex in the Land of Genghis Khan: From the Times of the Great Conqueror to Today - Terbish, Baasanjav (Lexington Books, 2023)
This book examines the history of sexuality in Mongolia over the last 800 years. As a culture-specific and time-specific system of values, practices and identities, sexuality in Mongolia, as elsewhere, has been subject to change as Mongolian society transformed from an empire to a post-imperial regional power to a Qing colony to a socialist country, before embracing liberal democracy in the 1990s. Since every social change tends to become reflected in sexuality, this study takes into account a range of intertwined topics, including religious ideologies, political ideologies, law, gender and relationships between individuals and the state, all of which have evolved throughout Mongolia’s history and require rethinking if one is to describe such a complex social phenomenon as human sexuality.